1992
DOI: 10.1084/jem.175.6.1483
|View full text |Cite
|
Sign up to set email alerts
|

Differential regulation of T cell antigen responsiveness by isoforms of the src-related tyrosine protein kinase p59fyn.

Abstract: SllnunaryRecent observations suggest that the src-related tyrosine protein kinase p59~ may be involved in antigen-induced T lymphocyte activation. As a result of alternative splicing, p59~ exists as two isoforms that differ exclusively within a short sequence spanning the end of the Src Homology 2 (SH2) region and the beginning of the tyrosine protein kinase domain. While one p59~ isoform (fynB) is highly expressed in brain, the alternative product (fynT) is principally found in T lymphocytes. To further under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
79
3

Year Published

1994
1994
2009
2009

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 146 publications
(84 citation statements)
references
References 29 publications
2
79
3
Order By: Relevance
“…Subsequently, it was found that the src nonreceptor protein tyrosine kinase (PTK), p59fy", may be mediating this effect, because it is overexpressed in DN T cells (36) (Figure 1). The significance of this novel observation is that the fyn kinase is associated with the CD3/T cell receptor (TCR) complex, and directly mediates the signal initiated by ligand binding (37,38) (Figure 1). It is interesting to speculate whether the constitutive tyrosyl phosphorylation actually reflects autophosphorylation of the fyn kinase.…”
Section: Aberrant Receptor-mediated Signal Transductionmentioning
confidence: 99%
“…Subsequently, it was found that the src nonreceptor protein tyrosine kinase (PTK), p59fy", may be mediating this effect, because it is overexpressed in DN T cells (36) (Figure 1). The significance of this novel observation is that the fyn kinase is associated with the CD3/T cell receptor (TCR) complex, and directly mediates the signal initiated by ligand binding (37,38) (Figure 1). It is interesting to speculate whether the constitutive tyrosyl phosphorylation actually reflects autophosphorylation of the fyn kinase.…”
Section: Aberrant Receptor-mediated Signal Transductionmentioning
confidence: 99%
“…To extract PAG and PAG-associated proteins from lipid rafts, cells were lysed in a buffer containing maltoside (1% n-dodecyl-␤-D-maltoside, 50 mM Tris [pH 7.6], 150 mM NaCl, and 2 mM EDTA) supplemented with protease and phosphatase inhibitors (6). Immunoprecipitations and immunoblot analyses were performed as previously described (7,33). Radioactivity was quantitated with a Storm PhosphorImager (Molecular Dynamics, General Electrics Canada, Mississauga, Ontario, Canada).…”
Section: Methodsmentioning
confidence: 99%
“…Primary antibodies used in this study were: rabbit polyclonal anti-netrin 1 PN3 (Manitt et al, 2001), mouse monoclonal anti-Dcc (G97-449; BD Biosciences Pharmingen, San Jose, CA, USA), goat polyclonal anti-Dcc (Santa Cruz Biotech, Santa Cruz, CA, USA), rabbit polyclonal anti-myelin basic protein (Mbp, Chemicon, Temecula, CA, USA), mouse monoclonal anti-Mbp (Chemicon), mouse monoclonal RIP antibody (Chemicon), mouse monoclonal anti-2Ј,3Ј-cyclic nucleotide 3Ј phosphodiesterase (Cnp, Sternberger Monoclonals, Lutherville, MD, USA), rabbit polyclonal antiMag (Chemicon), rabbit polyclonal anti-Nfm (Nefm -Mouse Genome Informatics) (Chemicon), rabbit polyclonal anti-Fyn (Upstate Cell Signaling, Charlottesville, VA, USA) used for western blots, rabbit polyclonal anti-Fyn [gift of Dr Andre Veillete and described previously (Davidson et al, 1992)] used for immunoprecipitation and western blots, mouse monoclonal anti-FAK (BD Biosciences), rabbit polyclonal anti-N-WASP (Santa Cruz), and rabbit polyclonal anti-phospho-Src (Cell Signaling), which recognizes the pY416 epitope in all SFK members.…”
Section: Antibodiesmentioning
confidence: 99%